Photobacterium damselae subsp. damselae, an Emerging Pathogen Affecting New Cultured Marine Fish Species in Southern Spain. - Labella Vera, Alejandro Manuel; Berbel, Concepción; Manchado, Manuel; Castro-López, María Dolores; Borrego-García, Juan José (InTechOpen, 2011)
Aquaculture is the fastest growing food-producing sector, accounting almost 50% of the world food fish demand. Considering the projected population growth over the next two decades, it is estimated that at least an additional 40 million tonnes of aquatic food will be required by 2030 to maintain the current per capita consumption (NACA/FAO, 2001). Marine aquaculture production was 30.2 million tonnes in 2004, representing 50.9% of the global aquaculture production (FAO, 2004). By major groupings, fish is the top group whether by quantity or by value at 47.4% and 53.9%, respectively. However, according to the World Aquaculture Society (WAS, 2006), the future of this sector must be based on the increase of scientific and technical developments, on sustainable practices, and, mainly, on the diversification of the cultured fish species. For this reason, the European Union has designed an innovative plan to increase the culture of new fish and shellfish species, mainly marine, maintaining the production of other consolidated species (UE, 2010)
Keywords: Acuicultura; Peces - Enfermedades bacterianas; Bacterias gram negativas; Virulencia (Microbiología); Photobacterium; Aquaculture; Virulence; Emerging; Cultured marine fish